T. H. White: A Critical Biography - THOMPSON, ANNE (Trinity College Dublin. School of English. Discipline of English, 2018)
This thesis is a critical biography of the author T. H. White. My purpose is to define the influences on his work throughout his life and set him in the historical and cultural context of the period from the 1930s through the 1950s. I trace his evolution as an author, the figures that shaped his work and inspired him, and, in particular, his tendency as a writer to imitate the work and attitudes of various literary figures with whom he came in contact. My methodology is predominately archival and draws on the significant repository of White?s papers, manuscripts, and other material lodged in the Harry Ransom Center, Texas, and at Queen?s College, Cambridge. This is the first study to use these archives to such an extent in order to discuss White?s oeuvre. My thesis is also unique in that it recognizes the importance of Ireland to the vast majority of the material published after 1939, when White chose to move there for the purpose of avoiding the Second World War. Ireland has hitherto been ignored as an influence on White?s work, yet it largely determined the production of his most famous novel, The Once and Future King, along with most of the books published in the final two decades of his life. Arguably, although he published nothing while he lived there, his six years in Ireland were the author?s most creatively productive period. The first chapter investigates the author?s engagement with concepts of England and pastoralism in the mid-1930s and situates White?s early work within the literary trend for rural revival in that decade. The chapter focuses primarily on England Have My Bones (1935), as this text represents a turning point in the author?s life: its moderate financial success encouraged him to leave his teaching position, and its critical reception introduced him to the author and critic David Garnett, who would become a close friend and mentor. This chapter also explores White?s interest in the concept of the ?gentleman? during this time, and ? in direct relation to this ? his meeting and correspondence with the poet Siegfried Sassoon in 1938. The second chapter investigates the impact of the Second World War on The Once and Future King (1958); it uncovers the means by which this text changed from a whimsical story about childhood to an anti-war treatise with a strong political message. The chapter also analyzes White?s interest in the work of Aldous Huxley, the author, and Julian Huxley, the biologist, and how their research on ants allowed White to conceptualize a biological rational for humanity?s tendency to wage war. The third chapter continues to explore the changes that the Second World War brought to The Once and Future King, and, in particular, how White constructed an Irish identity in order to justify his absence from the War. The chapter then evaluates the influence of Ireland on the characters and content of the epic. The fourth chapter goes into greater detail on the influence of White?s sojourn in Ireland by studying the two books about the country that White began during his stay: The Godstone and the Blackymor (1959) and The Elephant and the Kangaroo (1947). White attempts to align his own work with various ?Irish? genres of literature during his time in the country, and his extensive reading in Irish literature ? clearly documented in the archives ? indicates the motivations for his adoption of these two particular Irish identities. The fifth chapter shows how White returns to children?s literature with Mistress Masham?s Repose (1946) and The Master (1957) as he moves into a post-war and post-atomic age. It investigates how White uses the genre of children?s literature to examine dark and troubling concepts such as fascism, weapons of mass destruction, and authoritarian power. Once again the impact of Ireland is noted within this chapter, as both of these books were begun while White was still living in the country. The sixth chapter traces White?s creative decline in the final years of his life along with his growing financial success with the production of the musical Camelot (1960). It defines White?s final literary identity, that of the literary antiquarian, and explores the non-fiction books on which he labored during his final productive years: The Age of Scandal (1950), Scandalmonger (1952), and The Book of Beasts (1954). My thesis concludes that White?s work was deeply affected and contextualized by his time in Ireland, and shaped by a succession of specific literary influences and mentors. In situating his oeuvre largely within the cradle of the Second World War, I suggest that he was neither creatively disengaged from his generation nor isolated by his relocation to neutral Ireland. Instead, I demonstrate the extent to which his texts engage, serially, intensively and across a range of genres, with the major themes of nation, war, empire and authoritarianism that dominate this period in British and Irish culture.
APPROVED